Remittances and the Impact on Crime in Mexico - Steve Brito; Ana Corbacho; René Osorio (Inter-American Development Bank (IDB), 2014)
This working paper studies the effect of remittances from the United States on crime rates in Mexico. The topic is examined using municipal-level data on the percent of household receiving remittances and homicides per 100,000 inhabitants. Remittances are found to be associated with a decrease in homicide rates. Every 1 percent increase in the number of households receiving remittances reduces the homicide rate by 0.05 percent. Other types of crimes are analyzed, revealing a reduction in street robbery of 0.19 percent for every 1 percent increase in households receiving remittances. This decrease is also observed using a state-level panel in another specification. The mechanisms of transmission could be related to an income effect or an incapacitation effect of remittances increasing education, opening job opportunities, and/or reducing the amount of time available to engage in criminal activities.
hdl:11319/6482
Keywords: J15; J22; O12; O15; O54; 330; Remittances; Migration; Crime; Homicides; Mexico